I'm looking into rules of inference and in particular resolution, e.g.
$$((p ∨ q) ∧ (¬p ∨ r)) → (q ∨ r)$$
Now in the textbook I see the following example but I don't quite understand it
Show that the premises
(p ∧ q) ∨ r
andr → s
imply the conclusionp ∨ s
.
And here are the steps from the textbook to show this:
- Rewrite
(p ∧ q) ∨ r
as(p ∨ r) ∧ (q ∨ r)
- Rewrite
r → s
by the equivalent clause¬r ∨ s
- Using the resolution we can conclude
p ∨ s
Now I'm having a bit trouble understanding the above. To me the task is to show this:
$$((p ∧ q) ∨ r) ∧ (r → s) → p ∨ s$$
Now while I understand where first 2 steps come from, can't quite get my head around the 3rd one. After first 2 steps this is what we have (I think)
$$((p ∨ r) ∧ (q ∨ r)) ∧ (¬r ∨ s)$$
How it goes from here to conclude that
$$((p ∨ r) ∧ (q ∨ r)) ∧ (¬r ∨ s) → p ∨ s$$
is what I'm having hard time understanding.
I tried to use Commutativity
, Associativity
to go from
$$((p ∨ r) ∧ (q ∨ r)) ∧ (¬r ∨ s)$$
to
$$((r ∨ p) ∧ (¬r ∨ s)) ∧ (q ∨ r)$$
Here I see that the first part is a Resolution
:
$$((r ∨ p) ∧ (¬r ∨ s)) → (p ∨ s)$$
but can't understand what about: $$∧ (q ∨ r)$$